Assessment of Geriatrics Patients with Cardiovascular Disease Prescriptions for Appropriateness of Medications by Using Beers Criteria in Muhammadiyah Lamongan Hospital - Dyah Puspita Sari; Irma Susanti; Anisa Zulfa Fatihah (Universitas Airlangga, 2025)
Background: Number of geriatric residents has increased annually. Owing to pathological and physiological conditions, the geriatric population tends to consume more medications, thereby increasing their risk of adverse side effects and drug interactions. Objective: This study was to evaluate the appropriateness of therapy for outpatient geriatric patients with cardiovascular disease at Muhammadiyah Lamongan Hospital from August to October 2023. Methods: American Geriatrics Society (AGS) Beers Criteria are one of the tools used to identify drugs whose potential harm outweighs the expected benefits and should be avoided in the elderly population. This study employed a descriptive method, with retrospective data collection from secondary sources, including medical records and electronic prescriptions. Results: Findings revealed that out of 252 prescriptions for geriatric patients with cardiovascular disease, four types of medications were potentially inappropriate according to the Beers Criteria: nifedipine with 23 prescriptions (9.13%), amiodarone with one prescription (0.40%), digoxin with 13 prescriptions (5.16%), and diltiazem with four prescriptions (1.59%). Conversely, three types of medications were deemed appropriate: aspirin (96 prescriptions, 38.10%), digoxin (30 prescriptions, 11.90%), and diltiazem (11 prescriptions, 4.37%). In conclusion, of the 252 prescriptions reviewed for geriatric patients with cardiovascular disease, three types of drugs are appropriate, while four types increase the risk of potentially inappropriate treatment (PIM) based on the Beers Criteria. Conclusion: These findings underscore the need for careful consideration to mitigate the risk of drug reactions. If the medication cannot be used in geriatric patients, an alternative therapy should be used or a dose adjustment may be necessary.